Deficits during Voluntary Selection in Adult Patients with ADHD: New Insights from Single-Trial Coupling of Simultaneous EEG/fMRI - Karch, Susanne; Voelker, Julia Madeleine; Thalmeier, Tobias; Ertl, Matthias; Leicht, Gregor; Pogarell, Oliver; Mulert, Christoph (Frontiers in Psychiatry, 2014)
Deficits in executive functions, including voluntary decisions are among the core symptoms of ADHD patients. In order to clarify the spatio-temporal characteristics of these deficits, a simultaneous EEG/fMRI study was performed. Single-trial coupling was used to integrate temporal EEG information in the fMRI analyses and to correlate the trial by trial variation in the different ERP amplitudes with fMRI BOLD responses. The results demonstrated that during voluntary selection early electrophysiological responses (N2) were associated with responses in similar brain regions in healthy participants as well as in ADHD patients e.g. in the medial frontal cortex and the inferior parietal gyrus. However, ADHD patients presented significantly reduced N2 related BOLD responses compared to healthy controls especially in these frontal areas. These results support the hypothesis that in ADHD patients executive deficits are accompanied by early dysfunctions, especially in frontal brain areas.